VD_FINDINFO HC / 2013 / 553 vom 16. August 2013 - VD Tribunal cantonal (2013)
STIPULATION POUR AUTRUI, EXÉCUTION DE L'OBLIGATION, NATURE JURIDIQUE, EXÉCUTION EN NATURE | 112 al. 2 CO, 112 CO, 97 CO, 98 al. 1 CO, 98 al. 3 CO, 98 CO